Characterization of platinum group minerals in the UG-2 chromitite flotation concentrates from the western Bushveld complex, South Africa - Merkle, R.K.W. (Roland Karl Willi), 1954- (University of Pretoria, 2013)
Dissertation (MSc (Applied Mineralogy))--University of Pretoria, 2011.